PERAN KESADARAN LINGKUNGAN, NILAI-NILAI PRIBADI DAN PERILAKU PRO-LINGKUNGAN SEBAGAI VARIABEL MEDIASI TERHADAP NIAT GEN Z MEMBELI PRODUK ORGANIK - Prihatini, Hariati; J.E Sutanto (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
This study explores the influence of environmental awareness, personal values, and pro-environmental behavior on Generation Z’s intention to purchase organic products in Surabaya. Using the Theory of Planned Behavior (TPB) and Value-Belief-Norm (VBN) frameworks, the study highlights the role of pro-environmental behavior as a mediating variable. Data were collected through a quantitative survey involving 241 Generation Z respondents, employing purposive sampling techniques. The findings reveal that environmental awareness and personal values have a positive and significant influence on pro-environmental behavior. Pro-environmental behavior was also found to have a direct and significant impact on the intention to purchase organic products. Furthermore, environmental awareness and personal values more effectively influence purchase intentions indirectly through pro-environmental behavior. These results support TPB and VBN theories, emphasizing the importance of concrete actions in bridging the gap between awareness and purchase decisions. The practical implications of this research include the development of value-based marketing strategies that integrate environmental education with incentive programs to encourage pro-environmental behavior among Generation Z. This study contributes to the literature on Generation Z consumer behavior and provides new insights to support the growth of the organic product market in Indonesia.